Analysis of motivations for treatment of primary open-angle glaucoma - L.A. Zaporozhetc (РМЖ "Клиническая офтальмология")
L.A. Zaporozhets Leningrad Regional Clinical Hospital, St. Petersburg, Russian Federation Background: one of the keys to maintaining good vision in primary open-angle glaucoma (POAG) is regular use of medications to lower intraocular pressure (IOP). Many authors report that adherence to treatment in glaucoma ranges from 5% to 80%. The basic types of motivation are extrinsic and intrinsic. Intrinsic motivation is driven by human needs to achieve one's own well-being. In extrinsic motivation, the patient is influenced from outside and is considered more productive. Aim: to analyze the motivation for treatment in patients with early POAG. Patients and Methods: 60 patients (120 eyes) with early POAG were examined. All patients were prescribed IOP-lowering eye drops to maintain target IOP. Questionnaires were used to assess motivation for regular treatment. Patient complaints, presence or absence of optical coherence tomography abnormalities, presence or absence of ocular comorbidities, number of IOP-lowering medications used, number of instillations per day, and patient awareness of glaucoma were considered as potential motivators. Results: the effect of each factor on compliance was analyzed. High statistical power was achieved only for the evaluation of the effect of patient awareness of glaucoma. The study of the other factors listed above showed that, regardless of the degree of reliability of the results, they do not have a significant impact on compliance and therefore do not contribute to the emergence of motivation for regular instillation of IOP-lowering medications. Conclusion: widespread dissemination of information about the irreversible progression of glaucoma to blindness significantly increases patient motivation for treatment. Keywords: primary open-angle glaucoma, motivation, IOP-lowering therapy, optical coherence tomography. For citation: Zaporozhets L.A. Analysis of motivations for treatment of primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2024;24(3):116–120 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-3.